Improving students scientific literacy: a development of thematic ethnoscience-based teaching material - I Yuliana; Tjandrakirana Tjandrakirana; W Widodo (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This research aims to develop ethnoscience-based thematic teaching materials to improve students' scientific literacy. The procedure was divided into two phases; developmental phase and experimental phase. This developmental research used Four-D Model. However, within this research, the process of development would not involve disseminated as the last step. The teaching materials which were developed consist of a lesson plan, student handbook, student worksheet, achievement test and scientific literacy test. The experimental phase used one group pretest-posttest design. Results show that the validity of teaching materials which were developed was very good and revealed the enhancement of students activities with a positive response to the teaching-learning process. Furthermore, the learning materials increase the students' scientific literacy level.